Internalisasi Nilai Religius melalui Pembiasaan Salat Dhuha di Sekolah Dasar - Muhammad Choiru Zad; Prawidya Lestari; Ali Rohmat (MUADDIB: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the management of religious culture formation through the Dhuha prayer program at SD Negeri Salaman 4. The research focuses on the application of the POAC (Planning, Organizing, Actuating, and Controlling) functions in implementing the program to foster a robust religious culture among students. Adopting a qualitative approach with a descriptive design, data were gathered through in-depth interviews, participant observation, and documentation. The research subjects comprised the principal, teachers, and students. Data analysis involved data reduction, data display, and conclusion drawing, while the validity of the findings was ensured through source and technique triangulation. The results indicate that: (1) planning is executed through strategic meetings to define objectives, scheduling, and performance indicators; (2) organizing is structured through a clear, participative distribution of roles among the principal and teaching staff; (3) implementation is conducted through consistent habituation, uswah hasanah (role modeling), and positive reinforcement; and (4) controlling and evaluation are performed via clinical monitoring, attendance tracking, and periodic assessments to ensure program efficacy. The Dhuha prayer program has demonstrated a positive impact, manifesting in improved student discipline, habitual worship, and refined moral character. This study concludes that systematic management is a critical catalyst in transforming ritual practices into a sustainable and internalized religious culture within the elementary school environment.